Subsidiary debt, capital structure and internal capital markets☆ - Kolasinski, Adam C. (Journal of Financial Economics, 2009)
I study external debt issued by operating subsidiaries of diversified firms. Consistent with Kahn and Winton's [2004. Moral hazard and optimal subsidiary structure for financial institutions. Journal of Finance 59, 2537–2575] model, where subsidiary debt mitigates asset substitution, I find firms are more likely to use subsidiary debt when their divisions vary more in risk. Consistent with subsidiary debt mitigating the free cash flow problem, I find that subsidiaries are more likely to have their own external debt when they have fewer growth options and higher cash flow than the rest of the firm. Finally, I find that subsidiary debt mitigates the “corporate socialism” and “poaching” problems modeled in theories of internal capital markets.